Management of gallstone disease in children - Anna Orłowska; Piotr Socha; Monika Szychta; Hor Ismail; Irena Jankowska (Termedia Publishing House, 2023)
In recent years an increase in incidence of cholelithiasis in children has been observed. Among the various factors predisposing to the occurrence of cholelithiasis, some are modifiable and some are non-modifiable (including 25% of gallstones caused by genetic factors). One of the factors predisposing to the occurrence of cholelithiasis is obesity. The article describes the methods of prevention, diagnosis and treatment of uncomplicated and complicated cholelithiasis in children. Attention was paid to the new guidelines for the use of ursodeoxycholic acid in gallstone disease, as well as the molecular basis and research progress that has been made in this field.